ChemInform Abstract: Design, Synthesis and Anticancer Activity of N3, N11‐Bis(2‐hydroxyethyl)‐14‐aryl‐14H‐dibenzo [a, j]xanthenes‐3, 11‐dicarboxamide. Issue 29 (1st July 2013) - Song, Yongbin; Yang, Yihui; You, Jun; Liu, Bo; Wu, Lijun; Hou, Yunlong; Wang, Wenji; Zhu, Jiuxin
Abstract: Several title compounds show cytotoxicity in the micro‐ to submicromolar range.